Metode Massage Effleurage Pada Ibu Hamil Trimester II Dan III Untuk Mengurangi Nyeri Persalinan - Ula, Zumrotul; Delimayani, Delimayani; Fatimah, Siti; Yuliati, Luluk (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Childbirth is the process of expelling a fetus that occurs in a full-term pregnancy (37-42 weeks) and is born spontaneously with a posterior presentation that takes place within 18 hours without complications for either the mother or fetus. Effluent massage is a massage method to reduce pain during labor which is listed in the Summary of pain relief measures during labor, where in the first stage the latent phase (0-3 cm opening) and the active phase (4-7 cm opening) activities that can be carried out by the mother and companion during childbirth is effleurage. The aim of this Community Service is to increase the knowledge and skills of pregnant women in the second and third trimesters and birth attendants regarding Effleurage massage and to increase blood circulation, apply pressure and warm the abdominal muscles as well as increase physical and mental relaxation. The method of implementing this community service is by providing information and skills to pregnant women and their companions. The result of this service is that pregnant women and their companions understand and understand efflueurage massage and will apply efflueurage massage during the birthing process. The conclusion is that pregnant women and their companions will carry out effleurage massage during childbirth in order to provide a sense of comfort in dealing with labor pain.